Compound Dihuang Granule Inhibits Nigrostriatal Pathway Apoptosis in Parkinson’s Disease by Suppressing the JNK/AP-1 Pathway - Wang, Li; Yang, Yu-fang; Chen, Long; He, Zhu-qing; Bi, Dian-yong; Zhang, Lei; Xu, Yan-wu; He, Jian-cheng (Frontiers in Pharmacology, 2021)
Compound Dihuang Granule (CDG) is widely used in traditional Chinese medicine (TCM) for the treatment of Parkinson’s disease (PD). It has been shown to alleviate PD symptoms. However, the molecular mechanisms of its action have not been established. To establish the molecular mechanisms of CDG against PD, we used TCM network pharmacology methods to predict its molecular targets and signaling pathways, followed by experimental validation. The Core Protein protein interaction (PPI) network of the 150 intersections between CDG and PD-related genes, comprising 23 proteins, including CASP3 (caspase-3), MAPK8 (JNK), FOS (c-Fos), and JUN (c-Jun). KEGG and GO analyses revealed that apoptotic regulation and MAPK signaling pathways were significantly enriched. Since c-Jun and c-Fos are AP-1 subunits, an important downstream JNK effector, we investigated if the JNK/AP-1 pathway influences CDG against apoptosis through the nigrostriatal pathways in PD rat models. Molecular docking analysis found that the top three bioactive compounds exhibiting the highest Degree Centrality following online database and LC-MS analysis had high affinities for JNK. Experimental validation analysis showed that CDG decreased the number of rotating laps and suppressed the levels of phosphorylated c-Jun, c-Fos, and JNK, as well as the number of TUNEL positive cells and the cleaved caspase-3 level in the nigrostriatal pathway. Furthermore, CDG treatment elevated the number of TH neurons, TH expression level, and Bcl-2/Bax protein ratio in a 6-OHDA-induced PD rat. These findings are in tandem with those obtained using SP600125, a specific JNK inhibitor. In conclusion, CDG suppresses the apoptosis of the nigrostriatal pathway and relieves PD symptoms by suppressing the JNK/AP-1 signaling pathway.